Teaching And Learning the Concept of Tri Hita Karana in Early Childhood Education: Parents and Teacher’s Perceptions - I Made, Lestiawati (Sekolah Pascasarjana Universitas Negeri Jakarta, 2024)
This study focuses on describing the perceptions of teachers and parents towards the concept of tri hita karana in their learning practices. One of the goals of the tri hita karana concept is to care for the environment to create harmony and balance in the universe. This research was conducted in Early Childhood Education in Bali using qualitative methods through questionnaires and direct interviews with taxonomic data analysis techniques. The findings show that (1) The concept of tri hita karana in learning practice by teachers to children has not been fully implemented, (2) the concept of tri hita karana by parents to children has not been fully implemented in daily practice, (3) The perception of teachers and parents towards the concept of tri hita karana still requires understanding related to the concept and how to apply it.